Efecto del probiótico Bacillus subtilis sobre el crecimiento y alimentación de tilapia (Oreochromis niloticus) y langostino (Macrobrachium rosenbergii) en laboratorio - Gunther, Jorge (2004)
Effect of the probiotic Bacillus subtilis on the growth and food utilization of tilapia (Oreochromis niloticus) and prawn (Macrobrachium rosenbergii) under laboratory conditions. Three experiments were conducted to analyze the effect of the probiotic Bacillus subtilis on the growth of juvenile tilapia (Oreochromis niloticus) and freshwater prawn (Macrobrachium rosenbergii). The experiments were conducted under laboratory conditions, minimizing the indirect effects of the probiotic on the water quality and leaving only the possible bactericidal and digestion-support effects. A model of stress was also designed in tilapia to compare the effect with tilapia under normal conditions. The dose in the food was 0.1 % of the probiotic (5x108 CFU/g and 99.9 % maltrine) in the dry diet. Every 14 days the animals were weighed in group (tilapias ± 0.1 g, prawns ± 0.001 g) to estimate average body weight. In the first experiment (tilapia) the specific growth rate (SGR) and the feed conversion ratio (FCR) were bad in relation with the factor probiotic, but the differences were not significant. In the second experiment (tilapia) both the SGR and the FCR deteriorated with the addition of B. subtilis to the diet; the difference was significant to 94%. The stress factor, on the contrary, caused a notable worsening of both the growth and the food utilization. In the experiment with prawns the addition of B. subtilis caused a light deterioration of the growth and of the food utilization, with a statistical probability of mistake of 10% in case of the growth. During the experiment the direct effects over the digestive system should have prevailed, either by the contribution of macro- and micronutrients, or by the enzymes that contribute to the digestion. The negative effect due to the addition of the probiotic to the food was small (about 10% in both the SGR and the FCR) being difficult to detect statistically. The reports on the positive action of probiotics on the growth in aquatic animals have been conducted mainly in ponds, and our information does not contradict directly a possible positive action of B. subtilis in this type of systems. Since the effect on the digestive system seems to be relatively small, in those environments the effect might be compensated by other positive effects on water quality, and by bactericidal effects on pathogenic bacteria.